My even day - Fisher, Doris; Sneed, Dani.; Lee, Karen (Karen Jones), 1961- (Mt. Pleasant, SC : Sylvan Dell Pub., 2007)
A boy wakes up to find a strange day where everything is even, his mother has two heads, and a field trip turns into a very odd ordeal.
2.2
K-3
Keywords: Numeration -- Juvenile fiction; Number systems -- Fiction; Stories in rhyme; Numbers -- Fiction; Stories in rhyme